Gastrointestinal involvement and its association with the risk for nephritis in IgA vasculitis. (June 2021) - Sestan, Mario; Kifer, Nastasia; Frkovic, Marijan; Sapina, Matej; Srsen, Sasa; Batnozic Varga, Mateja; Ovuka, Aleksandar; Held, Martina; Gudelj Gracanin, Ana; Kozmar, Ana; Bulimbasic, Stela; Coric, Marijana; et al.
Background: We analysed clinical and biochemical parameters in predicting severe gastrointestinal (GI) manifestations in childhood IgA vasculitis (IgAV) and the risk of developing renal complications. Methods: A national multicentric retrospective study included children with IgAV reviewed in five Croatian University Centres for paediatric rheumatology in the period 2009–2019. Results: Out of 611 children, 281 (45.99%) had at least one GI manifestation, while 42 of 281 (14.95%) had the most severe GI manifestations. Using logistic regression several clinical risk factors for the severe GI manifestations were identified: generalized rash [odds ratio (OR) 2.09 (95% confidence interval (CI) 1.09–4.01)], rash extended on upper extremities (OR 2.77 (95% CI 1.43–5.34)] or face [OR 3.69 (95% CI 1.42–9.43)] and nephritis (IgAVN) [OR 4.35 (95% CI 2.23–8.50)], as well as lower values of prothrombin time (OR 0.05 (95% CI 0.01–0.62)], fibrinogen [OR 0.45 (95% CI 0.29–0.70)] and IgM [OR 0.10 (95% I 0.03–0.35)]] among the laboratory parameters. Patients with severe GI involvement more frequently had relapse of the disease [OR 2.14 (CI 1.04–4.39)] and recurrent rash [OR 2.61 (CI 1.27–5.38)]. Multivariate logistic regression found that the combination of age, GI symptoms at the beginning of IgAV and severity of GI symptoms were statistically significant predictors of IgAVN. Patients in whom IgAV has started with GI symptoms [OR 6.60 (95% CI 1.67–26.06)], older children [OR 1.22 (95% CI 1.02–1.46)] with severe GI form of IgAV (OR 5.90 (95% CI 1.12–31.15)] were particularly high-risk for developing IgAVN. Conclusion: We detected a group of older children with the onset of GI symptoms before other IgAV symptoms and severe GI form of the IgAV, with significantly higher risk for acute and chronic complications of IgAV.